Pola Komunikasi Keluarga dalam Film Pengabdi Setan 2: Communion - M. Andi Fikri (DIGICOM : Jurnal Komunikasi dan Media, 2023)
This research looks at the social codes used in the film Pengabdi Setan 2:Communion. In this study using a qualitative descriptive method approach with John Fiske's semiotic analysis. The results of this research show that the codes are based on the order of reality, the order of representation, and the order of ideology. This study found that there are three patterns of family communication used in the film: The Equality Pattern and The Balanced Split Pattern as well as the monopoly pattern. These patterns are shown through characterizations, images, and visual meanings.